(untitled) (Al Mustansiriyah Journal of Pharmaceutical Sciences, 2014)
In this study (300) blood samples were collected from healthy volunteer at national transfusion center, ministry of health, republic of Iraq, was examined for anti-Toxoplasma gondii antibodies by enzyme linked immunosorbent assay. The seroprevalence of anti-Toxoplasma gondii total IgG, IgM antibodies were 85 (56.6%), 40 (26.6%) respectively. While positive rate for IgG, IgM in female and male were 65 (43.3%), 35 (23.3%) and 20(13.3%), 5 (3.3%) respectively. The high positive rate of IgG and IgM appear in femle whoage rated between (21-30) and (31-40) years old, were 27 (25.7%), 7 (15.5%) respectively. Also rate of toxoplasmosis in married women greater than married men 27 (28.4%), 2 (1.9%).The same things for women cats breed, the rate of IgG and IgM was 24(44.4), higher thanmen who breed cats.